ELK4 transcription promotes MSI2‐mediated progression of non‐small cell lung cancer through the TGF‐β/SMAD3 pathway - Guo‐Cui Shi; Yu‐Qing Teng; Jin‐Song Zhu; Jia‐Wei Sun; Cui Liu; Yi‐Wei Zhang (Kaohsiung Journal of Medical Sciences)
Abstract Non‐small cell lung cancer (NSCLC) is a primary contributor to global cancer‐related mortality. Musashi‐2 (MSI2), an RNA‐binding protein (RBP), is upregulated in specific NSCLC tumor subgroups. The current investigation evaluated the role and underlying mechanism of MSI2 in NSCLC. The expression levels of ELK4, MSI2, SMAD3, p‐SMAD3 and TGFβR1 were assessed via RT–qPCR or Western blot. Chromatin immunoprecipitation (ChIP) and dual luciferase reporter assays were used to confirm the interaction between ELK4 and MSI2. The proliferation, migration and invasion of NSCLC cells were determined via MTT, colony formation, and transwell assays, respectively. A xenograft tumor model was established in BALB/c nude mice. Immunohistochemical (IHC) staining was used to test Ki67 expression. We found that MSI2 and ELK4 expression levels were increased in NSCLC tissues and cells. ELK4 depletion suppressed the proliferation, migration and invasion of NSCLC cells. ELK4 acts as a transcription factor and promotes the transcription of MSI2. MSI2 depletion repressed NSCLC cell proliferation, migration and invasion through the TGF‐β/SMAD3 pathway. Overexpression of ELK4 reversed the inhibitory effect of MSI2 repression on NSCLC progression. These results confirmed that ELK4 is a direct regulator of MSI2 expression and that MSI2 promotes NSCLC progression through TGF‐β/SMAD3 activation, suggesting the potential clinical value of inhibiting MSI2 in NSCLC.